The effect of oleic acid-enriched diet in hybrid groupers (Epinephelus fuscoguttatus × Epinephelus lanceolatus) upon infection with vibrio vulnificus using an LC-qTOF-MS approach - Natnan, Maya Erna; Low, Chen-Fei; Chong, Chou-Min; Rungrassamee, Wanilada; Baharum, Syarul Nataqain (MDPI, 2023)
The aim of this study was to evaluate the impact of oleic acid supplements on the liver metabolome of hybrid grouper fingerlings (Epinephelus fuscoguttatus × Epinephelus lanceolatus) challenged with Vibrio vulnificus. Oleic acid was used as a fish feed supplement because it has been reported to enhance the immune response of fish. After six weeks of feeding trials with the control and experimental diets (oleic acid immunostimulant), 10 fish were randomly selected from each treatment and challenged with V. vulnificus by immersion for 30 min. After seven days of post-bacterial challenge, the liver samples of surviving infected groupers were dissected and used for metabolomics fingerprinting using liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (LC-qTOF-MS). The results were then analyzed using MetaboAnalyst 5.0 and SIMCA+P software. From the analyses conducted, out of 639 primary metabolites detected, a total of 66 metabolites were significantly identified from the liver samples of grouper fed control and oleic acid diets. Further analysis also showed that the control and oleic acid diets have significantly different metabolites by the discriminating clustering of samples based on the PLS-DA analysis. Based on the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, the known metabolites pathways with high impact values are alanine, aspartate, and glutamate metabolism (0.13) followed by purine metabolism pathways (0.05). Moreover, out of these highly impacted metabolic pathways, L-glutamine (8.71%), L-lysine (4.05%), L-carnitine (11.53%), and inosine (10.49%) were the several metabolites that were highly abundant in the liver sample of surviving infected hybrid groupers fed with dietary oleic acid. The changes of metabolites contributed to improving the immune system of the fish. Thus, our results advance our understanding of the immunological regulation of the hybrid groupers’ immune response toward oleic acid immunostimulants against Vibrio infection.